102k views
4 votes
I honestly need help with these

I honestly need help with these-example-1
User Rax Adaam
by
4.3k points

1 Answer

2 votes

9. The curve passes through the point (-1, -3), which means


-3 = a(-1) + \frac b{-1} \implies a + b = 3

Compute the derivative.


y = ax + \frac bx \implies (dy)/(dx) = a - \frac b{x^2}

At the given point, the gradient is -7 so that


-7 = a - \frac b{(-1)^2} \implies a-b = -7

Eliminating
b, we find


(a+b) + (a-b) = 3+(-7) \implies 2a = -4 \implies \boxed{a=-2}

Solve for
b.


a+b=3 \implies b=3-a \implies \boxed{b = 5}

10. Compute the derivative.


y = \frac{x^3}3 - \frac{5x^2}2 + 6x - 1 \implies (dy)/(dx) = x^2 - 5x + 6

Solve for
x when the gradient is 2.


x^2 - 5x + 6 = 2


x^2 - 5x + 4 = 0


(x - 1) (x - 4) = 0


\implies x=1 \text{ or } x=4

Evaluate
y at each of these.


\boxed{x=1} \implies y = \frac{1^3}3 - \frac{5\cdot1^2}2 + 6\cdot1 - 1 = \boxed{y = \frac{17}6}


\boxed{x = 4} \implies y = \frac{4^3}3 - \frac{5\cdot4^2}2 + 6\cdot4 - 1 \implies \boxed{y = \frac{13}3}

11. a. Solve for
x where both curves meet.


\frac{x^3}3 - 2x^2 - 8x + 5 = x + 5


\frac{x^3}3 - 2x^2 - 9x = 0


\frac x3 (x^2 - 6x - 27) = 0


\frac x3 (x - 9) (x + 3) = 0


\implies x = 0 \text{ or }x = 9 \text{ or } x = -3

Evaluate
y at each of these.


A:~~~~ \boxed{x=0} \implies y=0+5 \implies \boxed{y=5}


B:~~~~ \boxed{x=9} \implies y=9+5 \implies \boxed{y=14}


C:~~~~ \boxed{x=-3} \implies y=-3+5 \implies \boxed{y=2}

11. b. Compute the derivative for the curve.


y = \frac{x^3}3 - 2x^2 - 8x + 5 \implies (dy)/(dx) = x^2 - 4x - 8

Evaluate the derivative at the
x-coordinates of A, B, and C.


A: ~~~~ x=0 \implies (dy)/(dx) = 0^2-4\cdot0-8 \implies \boxed{(dy)/(dx) = -8}


B:~~~~ x=9 \implies (dy)/(dx) = 9^2-4\cdot9-8 \implies \boxed{(dy)/(dx) = 37}


C:~~~~ x=-3 \implies (dy)/(dx) = (-3)^2-4\cdot(-3)-8 \implies \boxed{(dy)/(dx) = 13}

12. a. Compute the derivative.


y = 4x^3 + 3x^2 - 6x - 1 \implies \boxed{(dy)/(dx) = 12x^2 + 6x - 6}

12. b. By completing the square, we have


12x^2 + 6x - 6 = 12 \left(x^2 + \frac x2\right) - 6 \\\\ ~~~~~~~~ = 12 \left(x^2 + \frac x2 + \frac1{4^2}\right) - 6 - (12)/(4^2) \\\\ ~~~~~~~~ = 12 \left(x + \frac14\right)^2 - \frac{27}4

so that


(dy)/(dx) = 12 \left(x + \frac14\right)^2 - \frac{27}4 \ge 0 \\\\ ~~~~ \implies 12 \left(x + \frac14\right)^2 \ge \frac{27}4 \\\\ ~~~~ \implies \left(x + \frac14\right)^2 \ge (27)/(48) = \frac9{16} \\\\ ~~~~ \implies \left|x + \frac14\right| \ge \sqrt{\frac9{16}} = \frac34 \\\\ ~~~~ \implies x+\frac14 \ge \frac34 \text{ or } -\left(x+\frac14\right) \ge \frac34 \\\\ ~~~~ \implies \boxed{x \ge \frac12 \text{ or } x \le -1}

13. a. Compute the derivative.


y = x^3 + x^2 - 16x - 16 \implies \boxed{(dy)/(dx) = 3x^2 - 2x - 16}

13. b. Complete the square.


3x^2 - 2x - 16 = 3 \left(x^2 - \frac{2x}3\right) - 16 \\\\ ~~~~~~~~ = 3 \left(x^2 - \frac{2x}3 + \frac1{3^2}\right) - 16 - \frac13 \\\\ ~~~~~~~~ = 3 \left(x - \frac13\right)^2 - \frac{49}3

Then


(dy)/(dx) = 3 \left(x - \frac13\right)^2 - \frac{49}3 \le 0 \\\\ ~~~~ \implies 3 \left(x - \frac13\right)^2 \le \frac{49}3 \\\\ ~~~~ \implies \left(x - \frac13\right)^2 \le \frac{49}9 \\\\ ~~~~ \implies \left|x - \frac13\right| \le \sqrt{\frac{49}9} = \frac73 \\\\ ~~~~ \implies x - \frac13 \le \frac73 \text{ or } -\left(x-\frac13\right) \le \frac73 \\\\ ~~~~ \implies \boxed{x \le 2 \text{ or } x \ge \frac83}

User Mhopeng
by
5.2k points